Analisis Pencapaian Level Berpikir Geometri Van Hiele Siswa ditinjau dari Kemandirian Belajar dan Kepercayaan Diri - Herawati, Anisa; Zamzaili, Zamzaili; Sumardi, Hari (JEMS: Jurnal Edukasi Matematika dan Sains, 2023)
Thingking geometry is the placement of students based on their ability to understand geometric figures. Van Hiele’s theory states that student’s geometric thingking levels are sequentially through levels or levels, namely level 1 (analysis), Level 2 (abstraction), Level 3 (deduction) and Level 4 (rigor). This study aims to determine and describe the achievement of van hiele geometric thingking level in term of learning independence and self-confidence. The reasearch method used in this research is descriptive qualitative. The instrument used is a van hiele geomery test item and a questionnaire. The provision of test and questionnaires was carried out to students of SMPN 4 Bengkulu City for the 2021/2022 academic year. The results showed that the achievement of van hiele’s geometric thingking level was influenced by independent learning and self-confidence.